Society participation in the village fund program for development in Kletek village, Central Malaka sub-district, Malaka regency - Nahak, Jimy Handry; Kase, Petrus; Kelen, Pius Bumi (Goodwood Publishing, 2021)
Purpose: The purpose of this research was to describe and analyse society participation in the Village Fund for Development Program in Kletek Village, Central Malaka District, Malaka Regency. Research Methodology: This research is qualitative in nature. The informants who were selected purposively were 21 people. Results: The findings in this study are that society does not participate because the village apparatus is less open in capturing society’s aspirations, and there is no publication to the society so that it appears that government officials tend to be closed off about the use of funds. Limitations: The limitation of this research is that the research only focuses on the Kletek Village society’s participation in the Village Fund Program. Contribution: This research becomes scientific information for public administration program. Keywords: Participation, Decision making, Implementation, Use, Evaluation